2022
DOI: 10.3389/fpls.2022.954757
|View full text |Cite
|
Sign up to set email alerts
|

Forest fire monitoring via uncrewed aerial vehicle image processing based on a modified machine learning algorithm

Abstract: Forests are indispensable links in the ecological chain and important ecosystems in nature. The destruction of forests seriously influences the ecological environment of the Earth. Forest protection plays an important role in human sustainable development, and the most important aspect of forest protection is preventing forest fires. Fire affects the structure and dynamics of forests and also climate and geochemical cycles. Using various technologies to monitor the occurrence of forest fires, quickly finding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…With the rapid development of machine learning (ML), ML-based water quality assessment methods have become a hot research topic (Zheng et al, 2022). For example, Zhao, Z et al proposed a water quality assessment model based on a stochastic hybrid dynamic system (Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of machine learning (ML), ML-based water quality assessment methods have become a hot research topic (Zheng et al, 2022). For example, Zhao, Z et al proposed a water quality assessment model based on a stochastic hybrid dynamic system (Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of machine learning (ML), ML-based water quality assessment methods have become a hot research topic ( Zheng et al., 2022 ). For example, Zhao, Z et al.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been widely used in classification and prediction by scholars because it can dig out intrinsic relationships from large amounts of historical data for classification or prediction. Such as, deep learning [23,24], random forest (RF) [25], support vector machine (SVM) [26] and backpropagation neural network (BPNN) [27,28], and so on, have been gradually applied to prediction in various engineering fields because of its good accuracy. A comparative study was made by Liu et al [29] on the prediction of frost resistance of recycled concrete by using three methods, including ANN, Gaussian process regression, and multivariate adaptive regression spline; the results showed that, among the three methods, the prediction accuracy of ANN model is the best.…”
Section: Introductionmentioning
confidence: 99%
“…Fire-related loss of trees significantly increased (Figure 1). At present, methods of forest fire prevention mainly consist of patrolling, observation from watchtowers and subsequent satellite monitoring [1,2]. There are many problems with the fire protection personnel, such as inattention, absence from duty, inability to monitor in real-time and limited coverage.…”
Section: Introductionmentioning
confidence: 99%